PERANCANGAN MEDIA INTERAKTIF 3D VIRTUAL ENVIRONMENT SEBAGAI MEDIA INFORMASI PENGENALAN FASILITAS AKADEMIK UNIVERSITAS PRADITA - Fahrezi, Fachri; W.P Utomo, Nugroho; Pantow Gunawan, Ardi Makki (Kartala, 2021)
The introduction of information about academic facilities is still commonplace with print media such as posters, banners, banners, brochures, flyers and the like to digital media such as infographics, websites and social media. Following the development of technology trends, interactive virtual media is very popular because it has interactive feedback to the user and can be accessed through devices/gadgets. Pradita University still uses social media, Youtube and websites as its communication strategy in communicating academic facilities, these media cannot represent spatial matters. The design of Interactive 3D Virtual Environment media can answer this because this media can represent spatial information related to academic facilities virtually with full control by the user so that the user is directed to know the location of all academic facilities.